Engaging Native American publics
1 online resource (xi, 207 pages)
Keywords: "Engaging Native American Publics considers the increasing influence of Indigenous groups as key audiences, collaborators, and authors with regards to their own linguistic documentation and representation. The chapters critically examine a variety of North American case studies to reflect on the forms and effects of new collaborations between language researchers and Indigenous communities, as well as the types and uses of products that emerge with notions of cultural maintenance and linguistic revitalization in mind. In assessing the nature and degree of change from an early period of "salvage" research to a period of greater Indigenous "self-determination," the volume addresses whether increased empowerment and accountability has truly transformed the terms of engagement and what the implications for the future might be."--Provided by publisher.